Complete genome sequence of deformed wing virus and black queen cell virus isolated from honeybees ( Apis mellifera ) in Argentina - Gonzalez, Fernanda Noemi (2024)
We report the complete genome sequence of deformed wing virus and black queen cell virus isolated from Argentinean’s honeybees. These sequence data will be valuable for future research on the viral variants present in the country and the development of strategies to control the spread of these viruses in apiaries.